Experiences in anti-tuberculosis treatment in patients with multiple previous treatments and its impact on drug resistant tuberculosis epidemics - Biao Xu; Qi Zhao; Yi Hu; Ying Shi; Weibing Wang; Vinod K. Diwan (Taylor & Francis Group, 2014)
Background: Tuberculosis (TB) patients with a history of multiple anti-TB treatments are the 'neglected' group to the free anti-TB treatment policy in China. Objective: To understand the experiences of TB patients with multiple previous treatments with regard to bacteriological diagnosis and treatment regimens, especially for second-line anti-TB drugs, and how this might influence the risks of multidrug and extensively drug-resistant TB (M/XDR-TB). Design: A cross-sectional study was conducted in 10 county/district TB clinics in five provinces of China. The study participants were TB patients that had at least two previous treatment episodes that lasted longer than 1 month each. Face-to-face interviews and drug susceptibility testing (DST) were conducted with the consenting participants. Results: A total of 328 TB patients were recruited. The proportion of multidrug-resistant tuberculosis (MDR-TB) was 58.2% in the 287 DST-confirmed patients. Forty-two percent of the patients did not complete their first treatment course. About 23.8% of the participants had a history of taking second-line drugs, and more than 77.8% of them were treated in county TB dispensaries where only sputum microscopy was applied. Multivariate analysis found that the use of second-line drugs was significantly associated with frequency of previous treatments (p<0.01), but not with drug resistance profiles of patients. Conclusions: Patients with multiple previous treatments are at extremely high risk of MDR-TB in China. The unregulated use of second-line drugs bring about the threat of XDR-TB epidemic. DST-guided treatment and strict regulations of anti-TB treatment should be assured for the high-risk TB patients for the prevention and control of M/XDR-TB.